The impact of research and development subsidies on the employment of research and development inputs - Mestelman, Stuart; Shehata, Tawfik Mahmoud; McMaster University, Michael G. DeGroote School of Business, Innovation Research Centre (My University, 1996)
Investment in research and development may lead to reductions in a finn's production cost. If the production-cost savings associated with successful research and development is disseminated to other firms as soon as it is realized, too few resources may be allocated to investment in research and development. In such an environment, subsidies to investment in research and development may be justified. Three alternative subsidies schemes are considered. The most expensive scheme transfers a fixed amount of money per unit of investment undertaken. The next most expensive scheme transfers a fixed amount of money per unit of increase in investment from period to period, with no penalty for reducing investment from one period to the next. The least expensive scheme transfers a fixed amount of money per unit of increase in investment from period to period, but imposes a penalty of the same fixed amount of money per unit of decrease in investment from period to period. These schemes crudely capture characteristics of subsidy schemes used in the United States and Canada. The three schemes have different equilibrium predictions. All are Nash equilibria A laboratory implementation of this environment identifies the most expensive scheme (which transfers the greatest amount of money to firms) as yielding an outcome closest to the social optimal outcome.
24, [38] leaves ; Includes bibliographical references (leaves 23-24) ; "November, 1996"
The authors are pleased to acknowledge the financial support of this project by the Innovation Research Centre at McMaster University, the programming support from Rob Moir and Neil Buckley, and assistance in the conduct of laboratory sessions and tabulation of data by Neil Buckley. A version of this paper was presented at the October 1996 meetings of the Economic Science Association in Tucson. We benefitted from the comments of Neil Buckley, Ken Chan, Rob Moir, Andy Muller, and Jan Potters.
Keywords: Research and development tax credit > Canada Research Industrial > Canada Research Industrial > Canada > Management